Monthly mobility inferred from isoscapes and laser ablation strontium isotope ratios in caprine tooth enamel - N. Lazzerini; V. Balter; A. Coulon; T. Tacail; C. Marchina; M. Lemoine; N. Bayarkhuu; Ts. Turbat; S. Lepetz; A. Zazzo (Scientific Reports, 2021)
Abstract Strontium isotopic analysis of sequentially formed tissues, such as tooth enamel, is commonly used to study provenance and mobility of humans and animals. However, the potential of 87Sr/86Sr in tooth enamel to track high-frequency movements has not yet been established, in part due to the lack of data on modern animals of known movement and predictive model of isotope variation across the landscape. To tackle this issue, we measured the 87Sr/86Sr in plant samples taken from a 2000 km2 area in the Altai Mountains (Mongolia), and the 87Sr/86Sr in tooth enamel of domestic caprines whose mobility was monitored using GPS tracking. We show that high-resolution, sequential profiles of strontium isotope composition of tooth enamel reliably reflect the high-frequency mobility of domestic livestock and that short-term residency of about 45 days can be resolved. This offers new perspectives in various disciplines, including forensics, ecology, palaeoanthropology, and bioarchaeology.